BIRDS EYE 1-69, 23 January-7 February 1969. - Koester, R. W.; Freeman, R. F. (1969)
BIRDS EYE 1-69 was a regularly scheduled Arctic Ocean ice reconnaissance mission covering the North American sector of the Arctic Basin including peripheral seas east and west of Greenland and the Parry Channel in the Canadian Archipelago from 23 January to 7 February 1969. Ice observations were made under twilight or moonlight conditions. Excellent weather prevailed over the Arctic Basin and in the Canadian Archipelago. Weather conditions were extremely poor in other areas. Observations revealed a well-defined area of fractures and polynyas near the North Pole and a fracture zone at the mouth of Robeson Channel in the Lincoln Sea. In Parry Channel, fractures existed from Baffin Bay to Resolute; only three cracks were observed further westward to a point northwest of Banks Island. Extensive ice coverage observed on BIRDS EYE 8-68 (29 November - 16 December) continued to exist in the southern Greenland Sea. (Author) See also Report no. NOO-IR-69-36, AD-860 412.